Finite element analysis of foundation on layered and homogeneous soil deposit under dynamic loading - Verma A.K.; Mohanty S. (My University, 2025)
An earthquake force causes severe damages to civil engineering structures and their foundations. Geographical statistic shows that almost 54% area of India vulnerable to earthquake. Hence, it is very important to analyze dynamic response of the foundation. In the present study, an attempt has been made to study the behavior of foundation resting on layered and homogeneous soil deposit under dynamic loading condition. Two types of soil systems have been considered for the analysis; one is the layered soil system consisting of loose sand at the top, soft clay at the bottom and medium sand in between, and the other one is the homogenous soil system with soft clay. The effect of water table on soil foundation system of both layered and homogeneous soil systems has also been studied. The foundation considered for the analysis is shallow foundation (continuous footing). The dynamic loading considered for the analysis is of the recent Nepal earthquake (Mw-7.8). The modeling of the soil foundation system has been carried out using two-dimensional finite element software CyclicTP. The response of shallow foundation resting on layered and homogeneous soil deposit under dynamic loading condition is presented in the form of horizontal and vertical displacement; ground acceleration; excess pore pressure and excess pore pressure ratio; and shear stress versus shear strain at various locations. The results have been compared to understand the effect of layered and homogeneous soil on dynamic response of soil foundation. © Springer Nature Singapore Pte Ltd. 2021.